Phototropin-mediated perception of light direction in leaves regulates blade flattening. Issue 3 (4th September 2021) - Legris, Martina; Szarzynska-Erden, Bogna Maria; Trevisan, Martine; Allenbach Petrolati, Laure; Fankhauser, Christian
Abstract: One conserved feature among angiosperms is the development of flat thin leaves. This developmental pattern optimizes light capture and gas exchange. The blue light (BL) receptors phototropins are required for leaf flattening, with the null phot1phot2 mutant showing curled leaves in Arabidopsis ( Arabidopsis thaliana ). However, key aspects of their function in leaf development remain unknown. Here, we performed a detailed spatiotemporal characterization of phototropin function in Arabidopsis leaves. We found that phototropins perceive light direction in the blade, and, similar to their role in hypocotyls, they control the spatial pattern of auxin signaling, possibly modulating auxin transport, to ultimately regulate cell expansion. Phototropin signaling components in the leaf partially differ from hypocotyls. Moreover, the light response on the upper and lower sides of the leaf blade suggests a partially distinct requirement of phototropin signaling components on each side. In particular, NON PHOTOTROPIC HYPOCOTYL 3 showed an adaxial-specific function. In addition, we show a prominent role of PHYTOCHROME KINASE SUBSTRATE 3 in leaf flattening. Among auxin transporters, PIN-FORMED 3, 4, 7 and AUXIN RESISTANT 1 (AUX1)/LIKE AUXIN RESISTANT 1 (LAX1) are required for the response while ABCB19 has a regulatory role. Overall, our results show that directional BL perception by phototropins is a key aspect of leaf development, integrating endogenous and exogenous signals. Abstract : Phototropins perceive light direction in the leaf and control the auxin signaling pattern to regulate blade flattening.